Sacrifice your body - Ethridge, Roe; Andrew Kreps Gallery; Capitain Petzel (Gallery : Berlin, Germany) ([London] : MACK, 2014)
"Roe Ethridge's practice is that of a restless maverick and his constantly evolving visual sensibility has spawned a myriad of copyists in what has become known as 'the new school of synthetic photography'. In this his latest artist book, Ethridge conflates a rich array of photographic tropes, combining personal documentary images made in western Palm Beach County, his mother's childhood home, with surreal collage works, and a series discarded from a Chanel fashion shoot. These are interwoven with what appears to be a carefully directed scene depicting a teeth-white Durango SUV sinking into and then being retrieved from a canal. The clash of visual styles, histories and meaning establish a flatline of dissonance underscored by the touchline admonition of the neon title - SACRIFICE YOUR BODY." --Publisher's description
Title from cover.
A related exhibition of the same name was held at Andrew Kreps Gallery, New York and Capitain Petzel, Berlin, February 1-March 8, 2014.
boek
Keywords: Ethridge, Roe